Case Report: Disorder of Sexual Development in a Chinese Crested Dog With XX/XY Leukocyte Chimerism and Mixed Cell Testicular Tumors - Schwartz, Rebecca; Sugai, Nicole J.; Eden, Kristin; Castaneda, Caitlin; Jevit, Matthew; Raudsepp, Terje; Cecere, Julie T. (Frontiers in Veterinary Science, 2022)
A 10-year-old intact female Chinese Crested dog was presented for evaluation and further diagnostics due to persistent symptoms of vulvar swelling, vaginal discharge, and an 8-year history of acyclicity. At presentation, generalized hyperpigmentation and truncal alopecia were identified, with no aberrations of the female phenotype. Vaginal cytology confirmed the influence of estrogen at multiple veterinary visits, and hormonal screening of progesterone and anti-Mullerian hormone indicated gonadal presence. Based on findings from abdominal laparotomy and gonadectomy, the tissue was submitted for histopathology. Histopathologic evaluation identified the gonads to be abnormal testes containing multiple Sertoli and interstitial (Leydig) cell tumors. The histopathologic diagnosis of testes and concurrent normal external female phenotype in the patient lead to a diagnosis of a disorder of sexual development (DSD). A karyotype evaluation was pursued, and the molecular analysis revealed a mosaic pattern of normal 78,XX (80%) and 78,XY (20%) cells among the blood leukocytes, as well as a positive PCR test for the Y-linked SRY gene. Cytogenetic analysis of skin fibroblasts revealed the presence of 78,XX cells exclusively, and PCR tests for the Y-linked SRY gene were negative in the hair and skin samples. These results are consistent with an XX/XY blood chimerism (XX/XY). This is one of the few case reports of a canine with the diagnosis of leukocyte chimerism with normal female phenotypic external genitalia. This case illustrates a distinct presentation for hormonally active Sertoli cell tumorigenesis and demonstrates surgery as a curative treatment option for clinically affected patients.